Selection of Angiotensin I Converting Enzyme Inhibitory Peptides from Enzymatic Hydrolysate of Pinctada martensii Using Surface Plasmon Resonance - XIA Xiaoyu, WEN Caixing, CAO Wenhong, QIN Xiaoming, LI Yujin, LIN Haisheng, CHEN Zhongqin, ZHENG Huina, ZHU Guoping, GAO Jialong (Shipin Kexue)
Surface plasmon resonance (SPR) technology was used to analyze the binding of the three ultrafiltration fractions of the protein hydrolysate of Pinctada martensii (PHPM) with angiotensin I converting enzyme (ACE) as a protein ligand. The amino acid sequences of the bound peptides were identified by mass spectrometry (MS) and those with strong inhibitory potential against ACE were selected and synthesized. The in vitro ACE inhibitory activity and inhibition type of the peptides were studied as well as their interaction with ACE. It was found that the ultrafiltration fraction with a molecular mass of 3 000–5 000 Da had a strong binding signal to ACE. Among the four synthesized ACE inhibitory peptides, SLPWPMKPMNLIE had the lowest 50% inhibitory concentration (IC50) value and bound to the hydrophobic pocket of the C domain in ACE through hydrogen bonding.